Hubungan Pengetahuan Terhadap Sikap Family Caregiver dalam Merawat Penderita Stroke di Rumah - Erwin; Darussalam, Miftafu (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Background: The level of knowledge of family caregivers has a significant impact on caregiving behavior for stroke sufferers at home. Sufficient knowledge allows caregivers to make informed decisions regarding treatment options. On the other hand, a lack of knowledge can cause misunderstandings, discomfort, fear, decreased physical well-being, and psychological disorders. Aim: To determine the relationship between knowledge and the attitude of family caregivers in caring for stroke sufferers at home. Method: This research used cross-sectional techniques. The target population was family caregivers who care for stroke sufferers in the area Wirobrajan Health Center, Yogyakarta City. This sample used a simple random sampling method with a sample size of 42 respondents. The inclusion criteria consisted of respondents being family members who provide care for stroke sufferers at home and as nuclear family members. Exclusion criteria include family members who work in the health sector and stroke sufferers who receive homecare therapy. Results: Most of the family caregivers in the good knowledge category were 36 respondents (85.71%), and 23 respondents (54.76%) had a good attitude. The results of statistical tests using the gamma test showed that the p-value was 0.045 (p<0.05) and the correlation value was 0.774. Conclusion: There is a strong relationship between the knowledge and attitudes of family caregivers in caring for stroke sufferers at home. Implications: Family caregivers with good knowledge and attitudes in caring for stroke sufferers can improve recovery and prevent worse complications during home care.